Environmental Conscious Attitudes of Geography Education Students - Suciati, Suciati (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: The research aims to: 1) determine attitudes towards protecting the campus environment for Geography education students, 2) determine attitudes towards preserving the campus environment for Geography education students, 3) determine attitudes towards utilizing the campus environment for Geography education students. Methodology: The Geography education student population was 197 students, the sampling technique used purposive sampling with the characteristics of the 2006-2010 class of students who had taken PKLH, namely 50 students. The variables in the research are attitudes towards protecting, preserving and utilizing the campus environment for Geography education students. The data analysis technique uses descriptive percentages. Main Findings: The research results showed that as many as 90% of Geography education students were in the good category in being aware of the campus. Students have attitudes towards environmental protection such as views, feelings and efforts to plant trees and to attend seminars in the context of environmental protection on campus. Students have an attitude towards preserving the environment, such as having views, feelings and tendencies to act on waste management, reducing paper use and saving electrical energy on campus. Students have an attitude towards sustainable use of the environment, such as having views, feelings and tendencies towards action towards recycling rubbish, composting, using used goods on campus. Novelty/Originality of this study: Due to the fact that there are still some students who do not have an environmentally conscious attitude, this research examines the Environmental Conscious Attitude of Geography Education Students.